Natural language variables: variable-based semantic theories of pronouns and proper names - Przyjemski, K (2012)
Semanticists, philosophers and logicians have standardly analyzed a range of natural language expressions on the model of the variables of formal languages. This dissertation explores variable- based semantic theories of pronounsand proper names. The first two chapters argue that a variable-based, presuppositional semantics for pronouns proposed by Cooper (1979, 1983) resolves an apparent trilemma arising from the conjunction of three plausible commitments concerning the semantics of pronouns: that some anaphoric pronouns with quantifier antecedents are bound variables, that referential pronouns have context-independent meanings, and that the relation between bound and referential pronouns is not ambiguity or homonymy. The first chapter argues that Cooper’s semantics is descriptively and empirically superior to alternative theories, including Kaplan’s account, which does not resolve the trilemma. The second addresses an important objection to the view that bound and referential pronouns make the same semantic contribution, involving cases where bound pronouns do not appear to trigger semantic presuppositions. I argue that this appearance is misleading: bound pronouns do trigger semantic presuppositions and have the same (Cooper-style) denotations as referential pronouns. The third chapter addresses the phenomenon of non c-command or ‘donkey’ anaphora. These anaphors appear to require a departure from Cooper’s semantics and, more generally, from the view that anaphoric pronouns correspond to (classical) bound variables. I consider D-type accounts of donkey anaphora and argue that these accounts must be revised in ways that bring the denotations of donkey anaphors closer to those of ordinary bound and referential pronouns. The last chapter asks whether proper names require a variable-based semantics. I consider a pair of recent anaphoric theories of proper names, according to which proper names have anaphoric uses and are thus better modeled as variables. I argue that there are important reasons to reject a variable-based model for proper names, in contrast with pronouns.